Creativity and Leisure During COVID-19: Examining the Relationship Between Leisure Activities, Motivations, and Psychological Well-Being - Morse, K. F.; Fine, Philip A.; Friedlander, Kathryn J. (Frontiers in Psychology, 2021)
Social distancing policies have been implemented around the world to reduce the spread of coronavirus disease 2019 (COVID-19). These measures have included temporary restrictions on mass gatherings and the closure of public facilities, limiting the pursuit of leisure activities such as travel while allowing more time for at-home pursuits, including creative activities such as gardening and painting. Previous research has demonstrated the benefits of physical activity for psychological well-being during COVID-19, but less attention has been given to the potential benefits of creative pursuits, such as arts and music. The present study investigated changes in the pursuit of creative, non-creative, and physical leisure activities and the relationship between engaging in leisure, the motivations for and barriers to pursuing these activities, and psychological well-being during COVID-19. A total of 3827 participants from 74 countries completed an online leisure activities questionnaire and the World Health Organization Five Well-Being Index. Logistic regression indicated that gender, age, social distancing adherence, and employment status significantly predicted leisure engagement during COVID-19. Compared to sports and outdoor pursuits, participation in creative activities was generally more likely to increase during this period, while participation in non-creative activities was less likely to increase. Multiple linear regression indicated that maintaining or increasing time on leisure activities significantly predicted well-being during COVID-19, with increased time spent on home crafts and artisanship, fine arts, musical and performing arts engagement, sports and outdoor pursuits, niche and IT interests, and language activities each predicting higher well-being outcomes. Motivations such as seeking creative expression and mental stimulation, keeping fit, and maintaining social connections also predicted higher well-being. These findings suggest that participation in both physical and creative leisure activities may offer protective benefits for well-being during COVID-19, and that strategies to promote engagement in creative activities should also be considered in future guidance for mental health during periods of lockdown or isolation.